A positive COX-2/IL-1β loop promotes decidualization by upregulating CD82. Issue 3 (11th August 2021) - Qu, Qiu-Chan; Shen, Hui-Hui; Wang, Cheng-Jie; Zhang, Xin-Yan; Wu, Jiang-Nan; Lu, Hang-Cheng; Qiu, Xue-Min; Ding, Jia-Yi; Tan, Xiao-Fang; Liu, Li-Bing; Li, Ming-Qing
Abstract : A successful pregnancy requires sufficient decidualization of endometrial stromal cells (ESCs). CD82, a metastasis suppressor, is a critical regulator for trophoblast invasion but the effect in decidualization was largely unknown. Here we reported that there was a high level of CD82 in DSC by the immunohistochemistry staining and flow cytometer analysis. Stimulation with prostaglandin E2 (PGE2) elevated the expression of CD82 in ESCs. In contrast, celecoxib, a selective COX-2 inhibitor, significantly downregulated the expression of CD82 in decidual stromal cells (DSCs). Bioinformatics analysis and further research showed that recombinant human interleukin (IL)-1β protein (rhIL-1β) upregulated CD82 in ESCs. Of note, blocking IL-1β signaling with anti-human IL-1β neutralizing antibody could reverse the stimulatory effect of PGE2 on CD82 in ESCs. Silencing CD82 resulted in the decease of the decidualization markers PRL and IGFBP1 mRNA levels in DSCs. More importantly, we observed rhIL-1β also upregulated the expression of COX-2, and the upregulation of PRL and IGFBP1 induced by rhIL-1β could be abolished by celecoxib in ESCs or CD82 deficiency in DSCs. This study suggests that CD82 should be a novel promotor for decidualization under a positive regulation of the COX-2/PGE2/IL-1β positive feedback loop.